Non-invasive assessment of cerebral hemoglobin parameters in intracranial dural arteriovenous fistula using functional near-infrared spectroscopy—A feasibility study - Senthilvelan, Santhakumar; Kannath, Santhosh Kumar; Arun, Karumattu Manattu; Menon, Ramshekhar; Kesavadas, Chandrasekharan (Frontiers in Neuroscience, 2022)
Purpose: The purpose of the study was to assess the feasibility of noninvasive assessment of cerebral hemodynamics using functional near infra-red spectroscopy (fNIRS) in patients with intracranial dural arteriovenous fistula (DAVF) and correlate the hemodynamic changes with definitive endovascular treatment. Methodology: Twenty seven DAVF patients and 23 healthy controls underwent 20-minute task based functional near infrared spectroscopy and neuropsychology evaluation. The mean change in the hemoglobin concentrations obtained from the prefrontal cortex was assessed for the oxy, deoxyhemoglobin and oxygen saturation (HbO, HbR and SO2 respectively). The fNIRS data were analysed and correlated with improvement in neuropsychology scores at one month follow up. Results: There was significant reduction in the HbO in the patient group, while it increased in controls (-2.57E-05 vs 1.09E-04 mM, p<0.001). The reduced HbO in patients improved after the embolization with significance (-2.1E-04 vs 9.9E-04, p=0.05, q=0.05). In patients with aggressive DAVF (Coganrd 2B and above) , the change was highly significant (p<0.001; q=0.001). A moderate correlation was observed between MMSE scores and HbO changes (ρ - 0.4). Conclusion: fNIRS is a useful noninvasive modality in the assessment of DAVF the tool could potentially assist in bedside monitoring of treatment response.